Kebijakan Pemerintah Kabupaten Sukoharjo Untuk Rehabilitasi Rumah Tidak Layak Huni Sebagai Bentuk Dynamic Governence (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
: This research aims to determine the sustainability of the implementation of government policies in the rehabilitation of uninhabitable houses in Sukoharjo Regency. This type of research is empirical legal research or non-doctrial research to determine the conditions that occur in practice using a qualitative approach. The types and sources of research data consist of primary and secondary data. Data collection techniques were obtained through interviews and literature studies. The data analysis technique used is a qualitative data analysis model. The results of the research show that the continued implementation of government policy in the rehabilitation of uninhabitable houses in Sukoharjo Regency has had a positive impact on the people of Sukoharjo Regency. However, this program has not been able to address the housing backlog problem which is the main problem for the people of Sukoharjo Regency. Limited land is currently the main factor inhibiting backlog handling in the Sukoharjo Regency area.